Neurobehavioral characteristics of mice with SETD5 mutations as models of IDD23 and KBG syndromes - Nakagawa, Tadashi; Hattori, Satoko; Hosoi, Toru; Nakayama, Keiko (Frontiers in Genetics, 2023)
Genomic analysis has revealed that the genes for various chromatin regulators are mutated in many individuals with neurodevelopmental disorders (NDDs), emphasizing the important role of chromatin regulation in nervous system development and function. Chromatin regulation is mediated by writers, readers, and erasers of histone and DNA modifications, with such proteins being defined by specific domains. One of these domains is the SET domain, which is present in enzymes that catalyze histone methylation. Heterozygous loss-of-function mutations of the SETD5 (SET domain containing 5) gene have been identified in individuals with an NDD designated IDD23 (intellectual developmental disorder, autosomal dominant 23). KBG syndrome (named after the initials of the last names of the first three families identified with the condition) is characterized by features that either overlap with or are distinct from those of IDD23 and was initially thought to be caused only by mutations in the ANKRD11(ankyrin repeat domain containing 11) gene. However, recent studies have identified SETD5 mutations in some KBG syndrome patients without ANKRD11 mutations. Here we summarize the neurobehavioral characterization of Setd5+/− mice performed by four independent research groups, compare IDD23 and KBG phenotypes, and address the utility and future development of mouse models for elucidation of the mechanisms underlying NDD pathogenesis, with a focus on SETD5 and its related proteins.